Recombinant type Human mastadenovirus D85 associated with epidemic keratoconjunctivitis since 2015 in Japan. Issue 5 (15th February 2018) - Hashimoto, Shintaro; Gonzalez, Gabriel; Harada, Seiya; Oosako, Hideo; Hanaoka, Nozomu; Hinokuma, Rikutaro; Fujimoto, Tsuguto
Abstract : The aim of this study was to report the emergence of a recombinant human mastadenovirus (HAdV) type 85 (HAdV‐85) and to describe its genomic and clinical characteristics. The strains were detected and identified in Japan in cases of adenoviral conjunctivitis including epidemic keratoconjunctivitis (EKC). The type was designated as HAdV‐85 based on the novel combination of penton base ( P  = HAdV‐37), hexon ( H  = HAdV‐19), and fiber ( F  = HAdV‐8). The whole genome sequence determined for HAdV‐85 was compared against sequences of other types in the same species. The results of the phylogenetic analysis suggested a recombinant origin between HAdV‐53 and HAdV‐64, which have been two major causes of adenoviral EKC in Japan over the past decade. During the period between 2008 and 2016 in Kumamoto city, southwest of Japan, 311 cases diagnosed with conjunctivitis were diagnosed as being the consequence of adenoviral infections. Among them, 11 cases were determined to have been caused by HAdV‐85 since 2015. Thus, HAdV‐85 could be an emerging causative agent of adenoviral conjunctivitis.